Development of mucoadhesive buccal films from rice for pharmaceutical delivery systems - Siriporn Okonogi (2018)
The aim of this work was to investigate the suitable rice varieties for developing pharmaceutical buccal films. Two rice varieties with extreme difference in amylose content were used. Rice powders were chemically modified to yield the carboxymethyl rice prior to film preparation. Scanning electron microscope (SEM) and X-ray diffractometer (XRD) were used to investigate the solid structure of rice powders. The results indicated that amylose content in the rice grains played the effects on the morphology and crystalline structure of the modified rice powders as well as the film properties. The modified rice powders of low amylose content showed halo pattern XRD whereas some crystalline peaks could be observed from the high amylose content modified rice powders. Adding of glycerin caused the films better properties of more transparency and getting rid of air bubbles. High amylose rice films showed more transparency and higher mucoadhesive property and was considered to be suitable for incorporating the drug. Adding of surfactant caused the increase in tensile strength and decrease in elongation of the rice films. The most suitable surfactant for diclofenac buccal rice film is Tween 20. This study demonstrates that rice grains are the promising natural source for pharmaceutical film forming agent. Suitable pharmaceutical buccal films could be developed from the rice with high amylose content.